Repetitive transcranial magnetic stimulation in patients with hereditary spastic paraplegia [Herediter spastik parapleji hastalarlnda tekrarlayıcı transkraniyal manyetik stimülasyon uygulaması] - (:unkn) unknown (Turkish Neurosurgical Society, 2011)
Hereditary spastic paraplegia (HSP) is a heterogeneous genetic disease characterized by progressive spasticity of the lower extremities. Spasticity is a major cause of long-term disability in HSP and significantly affects functional life of patients. Repetitive transcranial magnetic stimulation (rTMS) is widely used in diagnosis and treatment of many neurological and psychiatric diseases. Although the positive impacts of rTMS for spasticity have been reported, no study has been found in HSP. The present here two HSP patients treated with low frequency rTMS [20 minutes at a frequency of 1 Hz (1200 pulses), for a period of 10 treatment sessions].
Keywords: Hereditary; Spastic paraplegia; Transcranial magnetic stimulation